The Positive Impact of Character Learning onEarly Childhood Behavior - Purnama, Mardiyah; Pauziah, Siti; Zulkarnain, Ali Iskandar; Afifah, Neela; Shobihah, Zuhroh (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
Character education in early childhood is a fundamental aspect in the formation of attitudes, morals, and social values that will be carried throughout life. In this phase, children's cognitive, emotional, and social development takes place very rapidly so that it requires appropriate stimulation from the family and school environment. This study uses a library research approach by examining various sources of literature, both print and digital, that are relevant to the theme of early childhood character education. The data collection process is carried out through a systematic review of books, scientific articles, and related publications. The findings show that character education has a significant influence on early childhood behavior, especially in aspects of emotion management, social interaction, and basic understanding of moral values. Character education that is integrated in the family and school environment is able to support the development of positive behavior of children. Character education plays an important role in shaping early childhood behavior. Therefore, parents and educators are expected to pay special attention and consistency in their application so that positive values can be embedded from an early age.